Sexual Offending: The Intrepid Professional-Adventurer and The Dejected Revenger-Victim - DeBlasio, Shannon (International journal of offender therapy and comparative criminology, 2024)
The Criminal Narrative Experience (CNE) is a framework developed within Invest-igative Psychology, which combines the emotions and narrative roles experienced by the offender during the commission of their offense, to understand their personal experience of crime . Previous research proposes four distinct themes within CNE; The Elated Hero, The Calm Professional, The Distressed Revenger, and The Depressed Victim, however little attention has yet been paid to the potential differences in themes across various offense types. The current study explored the CNE model within a sample of sexual offenders. Results found evidence of two CNE themes; The Intrepid Professional-Adventurer and The Dejected Revenger-Victim, this has implications stretching further than theorical, and are particularly poignant for therapists and treatment managers, who may be providing intervention to groups of sexual offenders at any one time.